Human Resource Management Strategy the Role of Managers and Career Development - Retno, Bayu; Samsuddin, Harun; Nitawati, Elly Yuniar; Soelistya, Djoko; Putrianti, Flora Grace (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The process of career development enables employees to identify their career goals within the context of human resource management strategies. Furthermore, the role of the manager is an important aspect to consider. The objective of this study is to ascertain the role of managers at PT XYZ in the career development of its employees. The research method employed was that of qualitative research using a case study model. This approach entails an in-depth and detailed investigation of a specific subject within a defined context, involving a single research subject, document, or event. The findings of this study indicate that PT XYZ's resource management has facilitated the career development of its employees through the implementation of continuous training programs, accompanied by a systematic evaluation process to ensure the efficacy of these programs in aligning with the needs of employee career development. Additionally, the role of the manager in the context of human resource management at PT XYZ has been identified as a crucial factor in this process. Furthermore, the organization has demonstrated its commitment to employee career advancement through the implementation of a promotion structure, which has been duly approved by the board of directors.